Exploring the Potential of Indigenous Grape Varieties for Sparkling Wine Production in the Hrvatska Istra Subregion (Croatia) - Tomislav Plavša; Marijan Bubola; Ana Jeromel; Ivana Tomaz; Marin Krapac (Beverages, 2025)
Indigenous grape varieties from the Hrvatska Istra subregion (Croatia) represent a significant proportion of regional wine production. In this study, the potential of six indigenous varieties—Malvazija istarska, Garganja, Duranija, Surina, Hrvatica, and Teran—for the traditional method for the production of sparkling wines was evaluated. Several of these varieties are currently underutilized or neglected in contemporary viticulture. A total of 85 volatile aroma compounds, including acids, alcohols, esters, C13-norisoprenoids, and terpenes, were identified and quantified using SPME-Arrow-GC/MS. Sensory evaluation was conducted using a structured nine-point hedonic scale. Among the compounds identified, C13-norisoprenoids (notably β-damascenone, TPB, and TDN) and esters (including ethyl 3-methylbutanoate, ethyl butanoate, and ethyl hexanoate) were found to contribute most significantly to the overall aromatic profile of the sparkling wines. Sensory profiles varied distinctly among the varieties. Some varieties demonstrated pronounced aromatic and structural characteristics, making them suitable for monovarietal sparkling wine production, while others exhibited complementary sensory properties more appropriate for cuvées. This study represents the first comprehensive chemical and descriptive sensory profiling of sparkling wines produced from these Istrian indigenous grape varieties. These findings aim to support their valorization and integration into the broader spectrum of sparkling wine production, thereby enhancing their recognition and market potential.